ALIH KODE DAN CAMPUR KODE PERCAKAPAN MAHASISWA DI PERPUSTAKAAN UNIVERSITAS PEKALONGAN - Erwan Kustriyono; M. Chamdi Rochmat (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Language is the most effective tool in the delivery of the message to others or hearer. The use  of  language  in  the  conversation  appears  a  message  which  is  conveyed  to  the opponent's speakers said. Conversations involving speakers and hearer will bring up the code-switching and code-mixing. These codes appear in  the conversation conducted by University  students  that  occurred  in  Pekalongan  University  library.  There  are  many factors  that  affect  the  transfer  of  those  codes.  The  factors  that  cause  dominant  code- switching in conversation at the library of the Pekalongan University are that the hearer factors and subject. Meanwhile, the dominant linguistic elements of code-mixing obtained in the conversation in the library of the Pekalongan University is the intangible elements of the inserted words and inserted phrases.  Keywordsi: code-switching, code-mixing and conversation